2022
DOI: 10.1016/j.amjoto.2022.103379
|View full text |Cite
|
Sign up to set email alerts
|

Auditory evaluation of infants born to COVID19 positive mothers

Abstract: COVID-19 infection can cause a wide spectrum of symptoms. The audio-vestibular system can also be involved, but there is still debate about this so findings need to be considered carefully. Furthermore, mother to fetus intrauterine transmission of COVID-19 infection in pregnant women is controversial. Few studies are available about the audio-vestibular symptomatology of newborns with intrauterine COVID19 exposure. Objectives This study investigates the possible correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
(27 reference statements)
3
17
0
3
Order By: Relevance
“…Furthermore, in the study by Ghiselli et al, only one child (1.9%) had bilateral refer results [29]. The above results are consistent with the JCHI indications that describe a reference standard of less than 4% for newborns that do not pass the first step of screening.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, in the study by Ghiselli et al, only one child (1.9%) had bilateral refer results [29]. The above results are consistent with the JCHI indications that describe a reference standard of less than 4% for newborns that do not pass the first step of screening.…”
Section: Discussionsupporting
confidence: 71%
“…Among these publications, Turkey is the major contribution, with 4 articles [7] , [21] , [26] , [28] . In the second place, 2 related papers were published from Italy [22] , [29] . Besides, there is 1 paper each from the United States and Egypt [25] , [27] .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that maternal SARS-CoV-2 virus infection does not affect newborn hearing [22] , [27] , [28] , [29] . Ghiselli et al investigated 63 newborns whose mothers had been diagnosed with COVID-19 during pregnancy and found that 4 failed the first ABR test, but only 1 (1.6 %) had ABR alterations when they were re-examined 1 month later [22] . Mostafa et al conducted a retrospective cohort analysis with 921 newborns, and only 1 of the 34 newborns born to COVID-19-positive mothers failed the ARB test (2.9 %) [27] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis of possible direct hearing damage has been explored through the audiological evaluation of newborns intrauterinely exposed to SARS-CoV-2. Nevertheless, a clear link between congenital infection and an increased risk of hearing loss has not been established [ 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%